A Study of Scheduling Algorithms in LTE -Advanced HetNet - Azheen Ghafour Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Long Term Evolution (LTE), known as 4G technology, is considered the choice for Third Generation Partnership Project (3GPP) and 3GPP2 mobile operators. LTE is expected to bring an improved user experience with full mobility support. However, to cope with the increasing number of mobile data subscribers that compete for the limited radio resources, effective network Quality of Service (QoS) mechanisms are necessary. A solution is to introduce small cells by adding low-power base stations to the existing macro- eNBs (Evolved Node B). The result is a Heterogeneous Network (HetNet) with large macro-cells combined with small cells (micro-, pico- and femto-cells) to cover areas not covered by the Macro-cells. Practically, HetNet is introduced in LTE-Advanced which is an extended version of LTE with more advanced features. Introducing HetNet in LTE-A brings challenges especially in terms of physical integration, QoS support and interference management. In this research, an architecture of HetNet integration is proposed. After that, some QoS scheduling algorithms are deployed for different types of on-going applications. Then, through the use of Riverbed Modeler, their performance parameters are studied with extensive simulations. Finally, an intensive comparison is done among the algorithms followed by a detailed discussion.